Pengaruh Media Kartu Ajaib Terhadap Keaktifan dan Hasil Belajar Siswa dalam Memahami Materi Sistem Tata Surya - Rosyidah, Rosyidah; Fajrie, Nur; Fathurohman, Irfai (Universitas Muria Kudus, 2024)
This study explores the development of Magic Card media to boost student engagement in solar system learning and facilitate conceptual understanding. The research is driven by the recognition that student participation is crucial for a successful learning environment. Therefore, designing relevant and engaging learning activities becomes essential. To address student participation and learning outcomes, the author created a media tool called Magic Card. This media involves group competitions where students match answer cards with planet nameplates and receive immediate feedback through magically lit lamps (correct = on, wrong = off). A classroom action research approach was employed in class VI of SDN Tanggultlare, involving a total of 11 students. The results revealed a significant improvement from the pre-cycle to cycle two. Student participation increased from 40.00% to 90.92%, and learning achievement rose from an average score of 67.55 to 85.45.